Conservative management of a 63-year-old athlete with a full-thickness tear of the second metatarsophalangeal plantar plate: A case report with 48 months follow-up - Jacek Cholewicki, PhD; Michael P Swords, DO; John M Popovich, Jr., PhD, DPT, ATC; Ryan S Fajardo, MD (Foot & Ankle Surgery: Techniques, Reports & Cases)
Plantar plate (PP) tears often necessitate surgical intervention to address concerns of progressive toe deformity and impaired function, particularly in the case of full-thickness PP tears or when conservative treatment fails. There is currently a lack of level 1 or 2 evidence regarding the efficacy of surgical versus non-surgical approaches to guide the management of plantar plate tears, especially for older individuals. This case presents a successful conservative management of a 63-year-old male recreational athlete/competitive skier with a full-thickness PP tear. The patient presented with a history of worsening pain around the left second metatarsophalangeal (MTP) joint, accompanied by a visible medial toe deviation and loss of toe purchase. Based on the history, physical exam, and MRI findings, the diagnosis of a subacute, full-thickness PP tear at the phalangeal attachment of the second MTP joint was made. During the surgical consultation, the patient was presented with both surgical and conservative treatment options and opted for conservative management. Conservative treatment consisted of avoiding activities requiring toe extension, carbon fiber insoles, a metatarsal pad, and sling taping of the toe for walking and other activities. He also performed daily toe plantarflexion stretches and used night splint taping with the second toe in 10-20 degrees of plantarflexion. At the 7-month follow-up, the patient was pain-free and had a notable reduction in toe deformity. The serial MRI findings revealed evolving scarring, with complete scar formation evident on the 19-month follow-up MRI. At the most recent follow-up, the patient remained physically active and pain-free 4 years after initiating treatment.